Optimalisasi Fasilitas Masjid melalui Corporate Social Responsibility Berbasis Kemitraan Internasional dan Kolaborasi Multipihak - Yuni Shara; Oktafiana Akmal; Harry Hidayat Kamil; Harun Ongah (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
−This community service initiative was carried out at the Al-Ikhlas Mosque, IDI Complex, Kwala Bekala Village, Medan Johor Sub-district, Medan City, North Sumatra. The partner organisation faced several challenges, namely the unsuitable condition of the caretaker’s house, the need for landscaping and greening of the mosque’s surroundings, limited social services for the community, and sub-optimal collaboration amongst stakeholders in the development of the mosque’s facilities. This initiative aimed to optimise the mosque’s facilities through the implementation of Corporate Social Responsibility based on multi-stakeholder collaboration, whilst simultaneously strengthening the community’s social, environmental and institutional functions. The programme was implemented using a participatory approach through the stages of needs identification, planning, multi-stakeholder coordination, implementation, and monitoring and evaluation. The initiative involved around 150 participants, comprising lecturers, students, mosque administrators, healthcare workers and members of the community, and comprised four main interventions: the construction of a caretaker’s house; the landscaping and greening of the mosque grounds; community health check-ups; and the strengthening of partnerships between national and international universities and the community. The results of the community service programme indicate that the entire series of activities was carried out as planned. The programme has resulted in the construction of caretaker’s houses, which is now in the implementation phase; the organisation of greening initiatives and the landscaping of mosque surroundings; the provision of healthcare services to the community; and increased community involvement in community work and the maintenance of facilities, as evidenced by observations, interviews and participatory evaluations. In addition to improving physical facilities, these activities have strengthened collaborative networks among stakeholders, laying the foundation for the programme’s sustainability. The successful implementation of this model remains dependent on the readiness of human resources, financial support and institutional commitment; consequently, its application in other locations requires adaptation to the characteristics and capacities of each partner.